Occupational disparities in survival in Korean women with cancer: a nationwide registry linkage study - Ichiro Kawachi; Hye-Eun Lee; Eun-A KIM; Masayoshi Zaitsu (BMJ Open)
Objectives We sought to examine occupational disparities in survival among Korean women diagnosed with cancer.Design Population-based, registry-linkage study.Setting South Korea.Participants Our study population comprised female workers registered in the Korean national employment insurance programme during 1995–2000 and diagnosed with cancer between 1995 and 2008. A total of 61 110 women with cancer diagnoses was included in analysis. The occupation was categorised into four groups: (1) managers, professionals and technical workers, (2) clerks, (3) service/sales workers and (4) blue-collar workers.Primary and secondary outcome measure Study population were linked to the national death registry until 2009. HRs for mortality adjusting for age and year of diagnosis were calculated in the study sample and subgroups with 10 specific cancer sites including thyroid, breast, stomach, cervix, colon or lung cancer using managers, professionals and technical workers as the reference.Results Women in service/sales (HR 1.25, 95% CI 1.15 to 1.35) and blue-collar occupations (HR 1.34, 95% CI 1.25 to 1.44) had poorer survival for all cancer sites combined, while blue-collar workers showed poorer survival for lung (HR 1.41, 95% CI 1.14 to 1.77), breast (HR 1.28, 95% CI 1.06 to 1.54), cervical cancer (HR 1.42, 95% CI 1.02 to 2.06) and non-Hodgkin’s lymphoma (HR 1.69, 95% CI 1.09 to 2.77) compared with women in professional and managerial positions.Conclusion We found substantial and significant inequalities in overall survival by the occupational group among Korean women with cancer, even in the context of universal access to cancer screening and treatment.